PENGARUH RISIKO BISNIS, PROFIT MARGIN, CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KESULITAN KEUANGAN PERUSAHAAN SEBELUM DAN SAAT TERJADINYA PANDEMI COVID-19 PADA PERUSAHAAN PROPERTI - Khirstina Curry (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This research aims to analyze how financial performance influences the possibility of financial difficulties. This research is quantitative. There are 6 variables consisting of 5 independent variables and 1 dependent variable from 2017 to 2017. 2021 on 8 property companies listed on the IDX. To analyze the influence of the independent variable on the dependent variable, secondary data, and Panel Data Regression analysis methods are used. The results of this research show that profit margins, corporate governance, leverage and pandemic conditions influence the occurrence of financial distress in property companies. Business risk is the only factor that does not influence the occurrence of financial distress